2016
DOI: 10.1186/s13287-016-0411-3
|View full text |Cite
|
Sign up to set email alerts
|

Local versus intravenous injections of skeletal muscle precursor cells in nonhuman primates with acute or chronic intrinsic urinary sphincter deficiency

Abstract: BackgroundMany factors may influence the efficacy of cell therapy for intrinsic urinary sphincter deficiency (ISD), including the route of administration of the cells and the condition of the sphincter. The goal of this study was to compare local versus intravenous administration of autologous skeletal muscle precursor cells (skMPCs) when administered to nonhuman primates (NHPs) with either acute or chronic ISD.MethodsThirty-two adult female monkeys were divided into eight groups (n = 4/group): (1) control; (2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 19 publications
2
16
0
Order By: Relevance
“…The rationale for these subgroup analyses was that these factors (age, body weight and social stress have been shown to influence the risk of diseases and been shown to influence, directly or indirectly the efficacy of cell therapies [812]. The major finding of this study was that the efficacy of skMPC therapy was reduced in older monkeys, in heavier monkeys and in monkeys with psychosocial stress – associated with reduced endogenous estrogen production.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…The rationale for these subgroup analyses was that these factors (age, body weight and social stress have been shown to influence the risk of diseases and been shown to influence, directly or indirectly the efficacy of cell therapies [812]. The major finding of this study was that the efficacy of skMPC therapy was reduced in older monkeys, in heavier monkeys and in monkeys with psychosocial stress – associated with reduced endogenous estrogen production.…”
Section: Discussionmentioning
confidence: 93%
“…We recently reported reduced efficacy of skMPCs in nonhuman primates (NHPs) with chronic (versus acute) intrinsic urinary sphincter deficiency (ISD) [8]. Senescence of stem cells, associated with aging is reported to dramatically reduce the effects of muscle regeneration and the efficacy of muscle cell therapy [9].…”
Section: Introductionmentioning
confidence: 99%
“…Assuming that mechanical injury/ dysfunction due to menopause or childbirth to be an important component of SUI, various investigators have injected bone marrow derived, mesenchymal or human amniotic fluid derived stem cells into the sphincter with varying results ( 7 ). A preclinical study has shown that both the chronicity of the intrinsic sphincter deficiency and the route of injection of stem cells (local vs. intravenous) affect the outcome with local injection being more effective ( 8 ). A randomized clinical trial published in 2007 ( 9 ) compared periurethral injections of autologous myoblasts and fibroblasts with conventional collagen in females with stress incontinence.…”
Section: Stress Urinary Incontinence (Sui)mentioning
confidence: 99%
“…Cynomolgus monkeys share with human beings a similar genitourinary anatomy and physiology, including the risk for age associated diseases . We have been able to produce chronic urinary sphincter dysfunction (ISD) in females of this species and successfully treat them with the chemokine CXCL12, which is a chemotactic factor for mesenchymal stem cells and plays an important role in angiogenesis . This finding provided the rationale for testing CXCL12 in a monkey model of post‐radical prostatectomy incontinence and erectile dysfunction.…”
Section: Introductionmentioning
confidence: 99%